Evaluation of the quality of e-payment services Study of a sample of clients of my company (Syriatel - Mtn) in Syria (Journal of Hama University, 2024)
This study aimed to assess the quality of electronic payment services provided by the two telecommunications companies (Mtn - Syriatel) through their electronic payment applications. The study relied on evaluating the quality of electronic payment services using a six-dimensional scale: "reliability - responsiveness - ease of use - privacy - security - offering and performance of the services platform". The researcher also relied on the analytical descriptive approach. Where the theoretical framework was built by reviewing the previous literature, and the questionnaire was used to collect primary data, and by using the simple random sample, the study sample consisted of 384 individuals from (Mtn - Syriatel) customers in Syria who use the electronic payment services it provides, Using appropriate statistical methods and SPSS V25 statistical analysis software, data were analyzed and hypotheses tested. The study concluded that customers' evaluation of the dimensions of the quality of electronic payment services provided to them via (Mtn - Syriatel) was at a high level, as the response averages were greater than the average of the five-point Likert scale adopted in this study.
Keywords: electronic payment - electronic payment services - quality of electronic payment services